2021
DOI: 10.1007/s00424-021-02537-y
|View full text |Cite
|
Sign up to set email alerts
|

The conduction velocity-potassium relationship in the heart is modulated by sodium and calcium

Abstract: The relationship between cardiac conduction velocity (CV) and extracellular potassium (K+) is biphasic, with modest hyperkalemia increasing CV and severe hyperkalemia slowing CV. Recent studies from our group suggest that elevating extracellular sodium (Na+) and calcium (Ca2+) can enhance CV by an extracellular pathway parallel to gap junctional coupling (GJC) called ephaptic coupling that can occur in the gap junction adjacent perinexus. However, it remains unknown whether these same interventions modulate CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 72 publications
5
22
2
Order By: Relevance
“…Further, simulations predict that a wide range of conduction velocities are possible during intermediate developmental stages due to variability in cellular/tissue properties and the relative timing of developmental changes. However, despite similar variability in parameter values, this variability in CV prediction narrows in adult tissue and is consistent with experimental measures (George et al, 2019;King et al, 2021). Interestingly, we see a larger influence of EpC effects in larger cell sizes with reduced GJ coupling, as would be the case in intermediate developmental stages and in adult myocardium for pathological conditions such heart failure (Smith et al, 1991;Peters et al, 1997;Yao et al, 2003;Akar et al, 2004;Poelzing and Rosenbaum, 2004), indicating a possible mechanism for maintained conduction during such transitional or diseased states.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Further, simulations predict that a wide range of conduction velocities are possible during intermediate developmental stages due to variability in cellular/tissue properties and the relative timing of developmental changes. However, despite similar variability in parameter values, this variability in CV prediction narrows in adult tissue and is consistent with experimental measures (George et al, 2019;King et al, 2021). Interestingly, we see a larger influence of EpC effects in larger cell sizes with reduced GJ coupling, as would be the case in intermediate developmental stages and in adult myocardium for pathological conditions such heart failure (Smith et al, 1991;Peters et al, 1997;Yao et al, 2003;Akar et al, 2004;Poelzing and Rosenbaum, 2004), indicating a possible mechanism for maintained conduction during such transitional or diseased states.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, we performed simulations with GJ conductance spanning from the low to high end of physiological measurements and hypothesized that such a range is qualitatively similar to different developmental stages and consistent with Cx43 expression changes. Importantly, the values chosen were consistent with experimental measurements of conduction for neonatal and adult myocardium (Rosen et al, 1981 ; George et al, 2019 ; King et al, 2021 ). We note that age-associated changes in GJ localization are represented as changes in GJ coupling (i.e., changes in f gap ), as all GJs are located at cell ends in the one-dimensional tissue model.…”
Section: Methodssupporting
confidence: 74%
“…This confinement leads to a screening effect which redirects extracellular current flow and thus enhances ephaptic coupling. Importantly, the range of perinexal widths leading to AP transmission is in line with previous experimental results (Veeraraghavan et al 2015(Veeraraghavan et al , 2018King et al 2021).…”
Section: Comparison With Previous Models and Studiessupporting
confidence: 90%
“…These studies also indicated that another mechanism occurs, known as self-attenuation, whereby the negative V e also brings V m closer to the Nernst potential of Na + , which decreases I Na and slows conduction. Optical mapping studies in isolated hearts, in which extracellular ion concentrations were changed and gap junction uncouplers were used, have yielded results that agree with the predictions of models incorporating ephaptic interactions (Veeraraghavan et al 2015King et al 2021). Using patch clamp experiments, we recently showed that restricting the extracellular space near cells expressing Na + channels affects I Na in a manner compatible with self-activation and self-attenuation (Hichri et al 2018).…”
Section: Introductionmentioning
confidence: 54%
“…Not only is the ionic homeostasis in cardiac cells essential for normal heart function, but abnormal extracellular ionic concentrations resulting from pathological conditions such as ischemia and renal failure could also promote arrhythmias, which indicates the need for further investigation. In addition, King et al [11] nicely demonstrated how the combined effects of Na + and Ca 2+ can differentially modulate conduction during hyperkalemia and how enhancing determinants of ephaptic coupling may attenuate conduction changes in various physiologic conditions.…”
mentioning
confidence: 99%